Urgensi Pemberlakuan Rezim Nasional Perlindungan Sumber Daya Genetik dan Pengetahuan Tradisional dalam Upaya Perlindungan Kearifan Lokal Provinsi Lampung - Melisa Safitri (Universitas Bandar Lampung (UBL), 2018)
Indonesia has valuable national assets, with more than 400 ethnic groups with cultural diversity and a wealth of natural resources and environment whose utilization and preservation is closely related to social life of local communities, so protection is needed to protect SDGPTEBT in Indonesia. From this background the author found 2 problem identification: first, what traditional knowledge has potential value in Lampung province. Second, the urgency of implementing the national regime for the protection of SDGPTEBT in the effort to protect the potential of the Lampung province's SDGPTEBT? The method used is a normative and empirical juridical approach. The procedure for data collection consists of library studies and field studies. While data processing is done by the method of editing, systematization and classification of data. The analysis used is qualitative analysis. Based on the results of the study, in general the traditional knowledge found in Lampung Province, among others, is agricultural knowledge, food recipes and traditional medicines, traditional house manufacturing, traditional cultural expressions of filter motifs, and environmental management of cat's eye. The urgency of SDGPTEBT protection must be carried out comprehensively through a national regime which is also supported by bureaucratic parties.